Screening For Multidrug-Resistant Staphylococcus Spp. Bacteria Causing Bacterial Vaginosis in Women: Penyaringan Bakteri Staphylococcus spp. yang Resisten terhadap Banyak Obat yang Menyebabkan Vaginosis Bakteri pada Wanita - Zainab A. Fadhil (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Bacterial vaginosis (BV) is a common vaginal condition characterized by a shift from lactobacilli dominance to opportunistic bacteria. Specific Background: Recent observations indicate the increasing role of Staphylococcus spp., particularly multidrug-resistant strains, in persistent or recurrent BV. Knowledge Gap: Limited evidence exists regarding species-level identification and resistance profiles of Staphylococcus spp. in BV cases in Iraq. Aim: This study aimed to identify the bacterial species associated with BV and determine the antimicrobial susceptibility of the most resistant isolates. Results: Among 50 clinical samples, 20 yielded bacterial growth, dominated by Gram-positive isolates (65%), especially Staphylococcus haemolyticus (40%), S. aureus (15%), and S. epidermidis (10%). Gram-negative isolates included E. coli (20%) and Klebsiella pneumoniae (10%). Gardnerella vaginalis was detected in 5%. Antibiotic testing of 16 isolates showed high multidrug resistance, with S. haemolyticus exhibiting resistance to OFX, CRO, AMC, CTX, EM, CFM, and NA. Novelty: This study provides the first localized profiling of MDR Staphylococcus spp. in BV using VITEK-2 confirmation. Implications: Findings highlight the need for routine species identification, antimicrobial stewardship, and region-specific treatment guidelines to prevent rising resistance and recurrence. Highlights• Dominance of MDR Staphylococcus spp. in BV• High resistance to β-lactams and macrolides• Importance of routine screening and antibiotic stewardship Keywords: Bacterial Vaginosis, Staphylococcus Haemolyticus, Multidrug Resistance, VITEK-2, Vaginal Microbiota